Kepala Madrasah sebagai Educator di Masa New Normal di MTs Darussalimin NW Sengkol - Abdul Waris Hamid; Subiantoro Subiantoro (MANAZHIM, 2022)
Madrasas are part of formal organizations where the head of the madrasa is the highest leader in a madrasa organization, of which employees, staff and students are members. A madrasa principal must have a role as an educator or as an educator. As an educator, you must have the right strategy in increasing educational professionalism. Most of the principals of madrasas are still unable to carry out their role as an educator, because they do not know what to do as an educator. The Head of Madrasah Tsanawiyah Darussalimun NW Sengkol, in carrying out his role as an educator, emphasizes three developments, namely first, mental development in fostering mentality, a madrasa head needs to make a regulation for teachers and students. As the head of Madrasah Tsanawiyah Darussalimin NW Sengkol did in the first instance, he carried out the existing regulations and students and teachers were given great appreciation for those who carried them out well. secondly, the moral development of the madrasah principal of MTs Darussalimin fosters the morale of students and teachers by doing a good job from himself, for example arriving early and throwing trash in its place. The third physical coaching physical development that is carried out is activating extra curricular at the madrasa.